HUBUNGAN ANTARA TINGKAT PENGETAHUAN DENGAN TINGKAT KEPATUHAN DALAM MENGGUNAKAN ALAT PELINDUNG DIRI PADA PETANI PENGGUNA PESTISIDA - Darmayanti, I Dewa Ayu Agung Inten; yasa, Ketut Tirta; Saputra, I Kadek (Coping: Community of Publishing in Nursing, 2015)
Abstract. Demands for improved quality and food quality resulted in pesticide use can not be avoided. Uncontrolled use of pesticides causes intoxication or poisoning problem is getting out of control. Pesticide poisoning should be able to be avoided by the use of appropriate APD comply. One of the originator factor of the compliance is knowledge that is very important domain for a person's actions. This study aims to determine the relationship between the level of knowledge with the level of compliance in the use of APD at farmer pesticide users in a Region Subak Kendran Village year 2015. This study used a descriptive correlational design with a "Crossectional" approach. The Sampling is by using purposive sampling with a sample of 32 people and the population is farmer pesticide users as many as 78 people. Collecting data in this study used a questionnaire. Results of statistical test by Spearman Rank correlation test with significance level of 95% at ? = 0.05 to variable levels of knowledge with the level of compliance in the use of PPE obtained results p = 0.000 means there is a significant relationship between farmers' knowledge with practical use of PPE. r= 0.636 indicates that the relationship is associated unidirectional, meaning that the decline followed a score of knowledge and practices that are less strong relationship.
Keywords: Compliance, Knowledge, PPE